Public awareness, knowledge and attitudes regarding the CEN system in South Australia - Heale, P.; Hawks, D.; Lenton, Simon (2000)
A sample of 605 South Australian residents was surveyed in 1997 regarding the Cannabis Expiation Notice (CEN) System.Thirty-nine percent had ever used cannabis and 14.5% used cannabis at least once a year. While only 17% knew of the CEN scheme, 76% were familiar with the 'on-the-spot fine' scheme. There was confusion about the legal status of two expiable offences; 24% thought possession of less than 100g of cannabis was legal and 53% thought growing three plants was legal. Only 40% knew that the two expiable offences involved some legal sanction. Regarding attitudes to cannabis law,the majority thought that growing 15 plants, selling 25g for profit, possession of less than 100g by a juvenile and driving while affected by cannabis should remain illegal. Eighty per cent thought medical use of cannabis should be legal. Half of the sample thought that growing three plants and possession of less than 100g of cannabis should be legal and most of those who thought the two offences should be illegal said a fine was the appropriate penalty. Most people (57%) thought the cannabis laws should either remain as they are or become less strict, indicating general support for expiation. [Heale P, Hawks D, Lenton S. Public awareness, knowledge and attitudes regarding the CEN system in South Australia.